Analysis of energy demand and household energy demand forecasting : a case of Bangladesh - Zaki, Rabiul Hossain; Lefevre, Thierry; Heredia, J. B.; Chen, X.; Keidenren Foundation, Japan (Bangkok : Asian Institute of Technology, 1994)
This study analyses the energy demand of Bangladesh in different sectors of economy of the last ten years ( 1982-1992) and forecasts the energy demand of household sector, which is the most energy consuming sector, for the next twenty years ( 1992-2012). Both economic and techno-economic approaches are employed, depending upon data availability, in the historical analysis to identify the trends, and understanding the major driving factors behind them. The energy demand of household sector is forecasted using the MEDEE-S model, which is a long term final energy demand simulation system for intermediate income countries. Two economic scenarios are combined with two energy policy scenarios to make four complete scenarios. Due to the predominance of traditional fuels, household energy demand is sensitive to end-use efficiency of cooking stoves, so the impacts of introducing more efficient stoves in the new energy policy is investigated. This is the only study on the energy demand analysis of Bangladesh, at any level, for almost ten years, and it is the first energy demand analysis of the country which attempts to employ the techno-economic approach.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Energy consumption -- Bangladesh -- Forecasting